PEMBINAAN PEMANFAATAN PEKARANGAN UNTUK KOMODITI HORTIKULTURA DI DESA GOHA KECAMATAN BATU MANDI KABUPATEN BALANGAN - Suparno Suparno; Ruben Tinting S; Ellen Christ Tambunan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
As an effort to improve the knowledge and skills of rural farmers, service activities have been carried out with the topic "Guidance on the Utilization of Yards for Horticultural Commodities in Goha Village, Batu Mandi District, Balangan Regency". it is difficult to meet the consumption needs of vegetables even though the land in the yard is still wide for direct use, so this sometimes has an unwanted negative impact such as the lack of intake of vitamins and minerals as well as dietary fiber, the lack of benefits of consuming vegetables, is also caused because of the ignorance of the farmers in an effort to utilize their yards by cultivating horticultural crops. This community service activity has been carried out with three methods, namely the lecture, written and demonstration methods.